The Laws of the Federation of Nigeria and Lagos, in force on the 1st day of June, 1958. - Nigeria (Lagos : Federal Govt. Printer, 1977)
The book is a compilation of various agencies established in accordance to the law of the Federation in 1977 when Lagos State was the Capital of Nigeria.
Cover title.
Reprint of selected chapters from 12 vol. set. Originally published: London : Printed by Eyre and Spottiswoode, 1959.
gp.22/01/2019
Loans
Keywords: Law